Lipolysis-Stimulated Lipoprotein Receptor Impairs Hepatocellular Carcinoma and Inhibits the Oncogenic Activity of YAP1 via PPPY Motif - Dong, Xin; Zhang, Xianbin; Liu, Peng; Tian, Yu; Li, Li; Gong, Peng (Frontiers in Oncology, 2022)
Purpose: Lipolysis-stimulated lipoprotein receptor (LSR) is a type I single-pass transmembrane protein which is mainly expressed in the liver. In this study we investigated if and how LSR is involved in the carcinogenesis of hepatocellular carcinoma (HCC). Experimental Design: To evaluate if LSR was abnormally expressed in human HCC tissues, and how its expression was associated with the survival probability of patients, we obtained data from Gene Expression Omnibus and The Cancer Genome Atlas Program. To investigate if and how LSR regulates the tumor growth, we knocked down and overexpressed LSR in human HCC cell lines. In addition, to evaluate the interaction between LSR and yes-associated protein1 (YAP1), we mutated LSR at PPPY motif, a binding site of YAP1. Results: Totally, 454 patients were enrolled in the present study, and high expression of LSR significantly decreased the probability of death. Knockdown of LSR significantly increased the expansion of HCC cells and significantly promoted tumor growth. In addition, downregulation of LSR increased the nuclear accumulation and transcriptional function of YAP1. Conversely, overexpression of LSR impairs this function of YAP1 and phosphorylates YAP1 at serine 127. Of note, mutation of LSR at the PPPY motif could block the interaction between LSR and YAP1, and restore the transcriptional ability of YAP1. Conclusions: The present study suggests that LSR binds to YAP1 via the PPPY motif. Thus, LSR increases the phosphorylation of YAP1 and impairs the growth of HCC. This highlights that targeting LSR might be a promising therapeutic strategy for HCC.